Electromyographic activity of the rectus abdominis during a traditional crunch and the basic jackknife exercise with the Ab Lounge - Nelson, Gail A; Bent-Forsythe, Denise A; Roopchand-Martin, Sharmella C (Journal of strength and conditioning research, 2012)
The use of nontraditional exercise devices such as the Ab Lounge™ has been promoted as being as effective as the traditional abdominal crunch in strengthening the abdominal musculature. Evidence for this is lacking, however. The purpose of this study was to compare the degree of activation of the upper and lower rectus abdominis using electromyography (EMG) during a traditional crunch with the basic jackknife using the Ab Lounge™. Twenty-two subjects (6 men and 16 women) were randomly selected from the student population at the University of the West Indies (Mona Campus). The mean age of the participants was 20.5 ± 1.5 years, height 166.4 ± 6.2 cm, weight 64 ± 10.3 kg, and waist-hip ratio 0.7 ± 0.1. Surface EMG was used to assess the muscle activity from the upper and lower rectus abdominis while each exercise was performed. The EMG data were full-wave rectified and normalized using a mathematical model that was set up in Microsoft Excel for Windows XP. Statistical analysis was performed on the data using a univariate analysis of variance with gender as a covariate. Significance was determined by p < 0.05. The mean EMG data recorded for the upper rectus abdominis was significantly higher with the traditional crunch when compared with the basic jackknife performed on the Ab Lounge™ (F = 4.39, p = 0.04). The traditional crunch produced a higher level of activity in the lower rectus abdominis when compared with the basic jackknife, but this was not statistically significant (F = 0.249, p = 0.62). There was no significant interaction between gender and the effect of the type of exercise on upper and lower rectus abdominis activation. These results suggest that the traditional abdominal crunch is more effective than the basic jackknife is in activating the rectus abdominis musculature.